Prevalence of Typhoid fever among the Children in a Semi Urban Area of Bangladesh (Journal of Dhaka Medical College, 2011)
Context: In Bangladesh, typhoid fever is a round the year problem which sometimes take epidemic proportions. The reason behind such occurrences are unsafe water supply, defective sewage system and unhygienic food handling practice. This study was designed to find out the prevalence of typhoid fever and related factors like sanitation facilities and food practice among the children of low income group people living in Kamrangir char and its adjacent areas in the semi urban Dhaka. Methodology: Data were collected from June 2009 to May 2010, from a sample of 96 patients with fever of more than seven days duration, who presented in the paediatric outpatient department of Dhaka Medical College Hospital, Dhaka. Detailed history, comprehensive physical examination and other relevant informations of the patients were recorded by following standard procedures. A raised anti O level with titre of >1:160 as well as other blood parameters were considered significant of having typhoid fever. Results: This study shows that 84(87.50%) patients had typhoid fever based on clinical examination and serological test results (widal test). It was observed that prevalence of enteric fever was high among the patients of school going age group (66.67%), habituated with unsafe drinking water (58.33%) and junk foods (72.92%). Statistical analysis showed that SSC level education in the parents who remain outside during the major part of the day for their livelihood had significant positive relationship with prevalence of typhoid fever. It was concluded that prevalence of typhoid fever was high among the children of school going age, who consume unsafe drinking water and food from outside source. Keywords: Typhoid fever; semi urban area; children. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8570 J Dhaka Med Coll. 2011; 20(1) :37-43